The behavioural biology of Argentine stem weevil in relation to host-plant characters : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Zoology at Massey University - Pilkington, Stephen (Massey University, 1987)
Literature on the biology, damage, and control of Argentine stem weevil (ASW), Listronotus bonariensis (Kuschel), is reviewed. Plant resistance with respect to control in other insects is reviewed in detail. Orientation, feeding and oviposition behaviour of ASW were investigated in relation to ryegrass. The visual and olfactory components of orientation were examined. Weevils did not discriminate between coloured nutrient agar plugs, nor between treatments in an olfactometer. Antennectomised weevils could discern between tissue from resistant ryegrass (infected with Acremonium lolii endophyte) and susceptible ryegrass (endophyte-free) when feeding, but not in the olfactometer. Host selection is probably mediated by a touch/taste system. The "apparency" of ryegrasses offers the most likely mechanism for location by ASW. ASW shows a gradation of feeding preferences between leaf tissue from twelve ryegrass cultivars. Annual cultivars were most preferred, then hybrids, perennials without endophyte, and lastly, perennials containing endophyte. In feeding trials with clonally replicated plants, weevils strongly preferred endophyte-free tissue. When restricted to endophyte-infected tissue, ASW feeds towards the leaf tip, where the lowest concentration of endophyte occurs. The amount of food consumed was inversely proportional to endophyte concentration. Weevils also prefer to feed on annual cultivars which have the least fibre and lowest tensile strength. Partial isolation of an extract that prevents ASW feeding, obtained from endophyte-infected ryegrass tissue after partitioning and dialysis, revealed a compound similar to "peramine". Age size, and sex of weevils made no difference to the amount of food consumed. Oviposition preferences paralleled feeding preferences in twelve ryegrass cultivars. Plant characteristics examined in relation to oviposition were endophyte concentration and distribution, age, fibre content, and tiller diameter. Endophyte concentration and fibre content in ryegrass sheath material followed a similar pattern, low in annuals, intermediate in hybrids and endophyte-free perennials, and high in endophyte-infected perennials. Tiller age had no effect on oviposition preference. Tiller diameter was positively correlated with oviposition preference, large diameter tillers (annual cultivars) being preferred. The behavioural components of oviposition are described, and evidence found which suggests a possible role for epideictic pheromones. The external receptors probably used in host-plant selection were identified and described. The antennae, mouthparts, tarsi, and ovipositor possess numerous sensilla, any of which could respond in the host selection process.
Keywords: Behavior; Argentine stem weevil